2002
DOI: 10.1159/000066086
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Gap Junction Proteins (Connexin 26, 30, 32, 43) in Normal Mucosa, Hyperkeratosis and Carcinoma of the Human Larynx

Abstract: Introduction: Gap junction proteins (connexins = Cx) form transmembrane channels and mediate the transfer of small molecules and ions between the cytoplasm of adjacent cells. Most tissues express several Cx isoforms. The precise combination might play an important role in the maintenance of cell differentiation. Human carcinogenesis is accompanied by aberrant expression and function of Cx. While the larynx is a target organ for many tumor promoters, no data on Cx expression in laryngeal mucosa are available. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 20 publications
2
14
0
Order By: Relevance
“…Very few studies have been reported about Cx43 expression in head and neck squamous cell carcinomas, mainly in laryngeal squamous cell carcinoma [19][20][21] In our paper, high or moderate Cx43 expression has been detected in overall well differentiated squamous cell carcinomas (G1), while low or negative Cx43 expression has been found in poorly differentiated carcinomas (G3): as expected, these data confirmed the relationship between low and high grade carcinomas and Cx43 expression.…”
Section: Discussionsupporting
confidence: 91%
“…Very few studies have been reported about Cx43 expression in head and neck squamous cell carcinomas, mainly in laryngeal squamous cell carcinoma [19][20][21] In our paper, high or moderate Cx43 expression has been detected in overall well differentiated squamous cell carcinomas (G1), while low or negative Cx43 expression has been found in poorly differentiated carcinomas (G3): as expected, these data confirmed the relationship between low and high grade carcinomas and Cx43 expression.…”
Section: Discussionsupporting
confidence: 91%
“…A lack of Cx32 in stratified squamous epithelium has also been described in the laryngeal tissue by Schneider et al (2002). Further studies are necessary to find out if the lack of Cx32 in the horse gastric squamous mucosa contributes to its high susceptibility to develop peptic ulcers.…”
Section: Discussionmentioning
confidence: 94%
“…10 Adherens junctions and desmosomes were also observed consistent with their presence in humans. [10][11][12] However, despite the presence of intercellular …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in addition to demonstrating an epithelial phenotype, candidate tissue constructs must also demonstrate the presence of important components of the epithelial barrier, including intercellular junctions. The native vocal fold epithelium contains intercellular junctions, including tight junctions, 10,11 gap junctions, 12 adherens junctions, 11 and desmosomes. 10 While Long and colleagues 9 reported the presence of e-cadherin, a marker of adherens junctions, in their model, further evidence of intercellular junctions was not provided.…”
Section: Introductionmentioning
confidence: 99%